Screening of Antibacterial Activity of Durio zibethinus Murr. Leaves Extract - Ulfa Malinda, M. Yasir (Universiti Malaysia Sarawak (UNIMAS), 2018)
Local durian or Durio zibethinus Murr. (D. zibethinus Murr) is a large edible fruit that currently well known in Indonesia, Philiphine, Malaysia and Southern Thailand. D. zibethinus Murr. is the species under Bombacaceae family. Many studies has been done towards the fruit flesh, its skin and the seed of this tree for the antibacterial activity. However, there are lacking on studies on leaves although the leaves was abundantly found. The present study, D. zibethinus Murr. leaves extract has been prepared using three different solvent which are ethanol, methanol and acetone and tested against two gram positive bacteria (S. aureus and B. cereus) and two gram negative bacteria (E. coli and P. aeruginosa) by using agar well diffusion method in order to looks for antibacterial activity. Different concentration of stock solution was prepared which are 62.5 mg/ml, 125 mg/ml, 250 mg/ml and 500 mg/ml using 10% DMSO. Gentamicin has been choosen as positive control and 10% DMSO as negative control. The inhibition zone were exhibitely found on gram positive bacteria from the D. zibethinus Murr. leaves extract. The diameter of inhibition zone were measured in milimeter (mm). Therefore, from the result obtained, further research on D. zibethinus Murr. Leaves should be conducted due to its potential in inhibit the gram positive bacteria and has high potential in medical application.